Global evidence on occupational sun exposure and keratinocyte cancers: a systematic review. (1st February 2021) - Loney, T.; Paulo, M.S.; Modenese, A.; Gobba, F.; Tenkate, T.; Whiteman, D.C.; Green, A.C.; John, S.M.
Summary: Individual studies have suggested that the association between occupational exposure to solar ultraviolet radiation (UVR) and the development of keratinocyte cancers (KCs) may only be valid in populations of European ancestry living in certain geographical regions. Comparative global data are scarce and so this review aimed to summarize current evidence on the association between occupational exposure to solar UVR and the development of KCs, with a specific focus on geographical location and skin colour. Ovid MEDLINE, PubMed, Embase and Web of Science were searched for potentially relevant records. Extracted data were summarized by study, country and region. We included one prospective cohort study and 18 case–control studies ( n = 15 233) from 12 countries in regions where the majority of the population is white skinned (Americas, Europe and Oceania). Eighteen of the 19 studies reported effect estimates suggesting an increased risk of basal cell carcinoma (BCC) and/or squamous cell carcinoma (SCC) among outdoor workers. Only 11 studies found a significantly increased risk and many had imprecise estimates. There was a significantly increased risk of BCC and SCC in individual studies in North America, Latin America and the Caribbean, Western Europe and Southern Europe, but not across regions or countries. Overall, 95% of studies reported higher risks among outdoor workers, although the increases in risk were statistically significant in just over half of the studies. Well‐designed and sufficiently powered occupational case–control and cohort studies with adequate adjustment for confounding factors and other risk factors are required to provide more accurate risk estimates for occupational KC.